2021
DOI: 10.1101/2021.12.03.471088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tumor protein D54 binds intracellular nanovesicles via an amphipathic lipid packing sensor (ALPS) motif

Abstract: Tumor Protein D54 (TPD54) is an abundant cytosolic protein that belongs to the TPD52 family, a family of four proteins (TPD52, 53, 54 and 55) that are overexpressed in several cancer cells. Even though the functions of these proteins remain elusive, recent investigations indicate that TPD54 binds to very small cytosolic vesicles with a diameter of ca. 30 nm, half the size of classical transport vesicles (e.g. COPI and COPII). Here, we investigated the mechanism of intracellular nanovesicle capture by TPD54. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…First, we will study the ALPS motif that allows curvature sensing by the ArfGAP1 protein, 30 and is also found on other proteins. [31][32][33][34] Since its discovery, ALPS has served as an important model peptide in many computational studies on curvature/lipid packing sensing, [35][36][37] also in our own group. 12,13 Second, we will include an amphipathic helix (AH) that was derived from the NS5A protein of hepatitis C virus (HCV) and discovered to sense and rupture vesicles in a size-dependent manner: small vesicles (including HCV particles themselves) were more readily ruptured than bigger ones and this size range overlaps with the diameter of many enveloped viruses (50-160 nm).…”
Section: Resultsmentioning
confidence: 99%
“…First, we will study the ALPS motif that allows curvature sensing by the ArfGAP1 protein, 30 and is also found on other proteins. [31][32][33][34] Since its discovery, ALPS has served as an important model peptide in many computational studies on curvature/lipid packing sensing, [35][36][37] also in our own group. 12,13 Second, we will include an amphipathic helix (AH) that was derived from the NS5A protein of hepatitis C virus (HCV) and discovered to sense and rupture vesicles in a size-dependent manner: small vesicles (including HCV particles themselves) were more readily ruptured than bigger ones and this size range overlaps with the diameter of many enveloped viruses (50-160 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies have examined how TPD54 binds INVs. Reynaud et al [ 27 ] found that TPD54 has sequences corresponding to four amphipathic helices (AH1-4) downstream of the coiled-coil region. The third helix (AH3) corresponds to an amphipathic lipid packing sensor (ALPS) motif which is known to govern membrane binding in a curvature-dependent manner [ 28 ].…”
Section: Intracellular Nanovesiclesmentioning
confidence: 99%
“…Overall, this downstream region is disordered; however, when TPD54 protein is incubated with liposomes, TPD54 becomes ordered upon binding to the membrane. Both studies showed that TPD54 has a preference for high curvature membranes in vitro [ 24 , 27 ]. The ALPS-containing AH3 is crucial for binding [ 27 ].…”
Section: Intracellular Nanovesiclesmentioning
confidence: 99%
See 2 more Smart Citations